2020
DOI: 10.1002/brb3.1745
|View full text |Cite
|
Sign up to set email alerts
|

Risk, resilience, psychological distress, and anxiety at the beginning of the COVID‐19 pandemic in Germany

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
338
12
33

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 382 publications
(426 citation statements)
references
References 24 publications
(32 reference statements)
43
338
12
33
Order By: Relevance
“…Increased anxiety in adults during epidemiological events is not uncommon and has been observed previously, e.g., during the H1N1 pandemic in 2009-2010 [49][50][51]. Unsurprisingly, it has also been reported during the COVID-19 pandemic [52][53][54].…”
Section: Discussionmentioning
confidence: 52%
“…Increased anxiety in adults during epidemiological events is not uncommon and has been observed previously, e.g., during the H1N1 pandemic in 2009-2010 [49][50][51]. Unsurprisingly, it has also been reported during the COVID-19 pandemic [52][53][54].…”
Section: Discussionmentioning
confidence: 52%
“…Again female gender and younger age were risk factors for anxiety and depression ( Solomou and Constantinidou, 2020 ). In Germany over 50% expressed suffering from anxiety and psychological distress ( Petzold et al, 2020 ). In Italy the prevalence of depression and anxiety symptoms was 24.7% and 23.2%; 42.2% had sleep disturbances and, among them, 17.4% reported moderate/severe insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies published during the current COVID-19 pandemic have focused on psychological distress in the general population and few have focused on individuals with a pre-existing psychiatric disorder. Several studies focusing on the current situation demonstrated that the pandemic and the lockdown increased anxiety and depression in the general population ( Fullana et al, 2020 )( Petzold et al, 2020 )( Salari et al, 2020 )( Wang et al, 2020 )( Xiong et al, 2020 ). Different factors which may influence this increase in anxiety, stress and depression include: duration of lockdown and social distancing, lack of psychological or physical coping strategies, facing great changes, financial issues, changes in sleep and dietary patterns, and disruption of daily routines, amongst others ( Salari et al, 2020 ).…”
Section: - Introductionmentioning
confidence: 99%